Management Information System - Human Resource & Payroll System for Sri Lanka Ports Authority - K J Lokugama, (International Journal of Engineering and Management Research, 2021)
Payroll is the one of most critical process in every large organization; it has many functionalities to fulfill on time for a smooth payroll process. When the number of employees varies on time to time due to retirements and new appointments and calculation method differs based on it, increases the complication of the system. Management operations concerning data can be a complicated scenario when the amount of data involved is large. More importantly, when the data involved requires a high level of accuracy, then the management role becomes hectic. Payroll is a sector of the management in which accuracy is required and a lapse in the data can lead to adverse effect on employee motivation and production. In such system, cost estimation is very vital for top management proceed with future organizational plans.